Annual Report 2015: Change for the better - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
In 2015, agriculture gained prominence in the global climate agreement, and CCAFS science increasingly informed initiatives to enhance millions of farmers’ resilience to climate impacts and help them reduce emissions. Visit the online report at http://bitly.com/ccafs2015 or download the PDF version.